2007
DOI: 10.1097/meg.0b013e328220eae0
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 and 2 gastric carcinoid tumors: long-term follow-up of the efficacy of treatment with a slow-release somatostatin analogue

Abstract: Little is known about the long-term results of treating gastric carcinoid tumors with a slow-release somatostatin analogue. We report three patients with type 1 and 2 gastric carcinoid tumors who were treated in the above mentioned way and followed for 27-50 months. In all cases, alternative endoscopic or surgical management was considered but deemed inappropriate. Treatment with a slow-release somatostatin analogue was begun in light of a favorable recent report. The result was regression or complete disappea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Proposals of TIGC management also include programs with different treatments according to TIGC number and size, performing surgery in cases of large polyps or frequently recurring multiple lesions, thus limiting a conservative approach to non-recurring cases of few small TIGCs [20,39]. On the other hand, promising results have been reported by SAs in selected patients having small multiple TIGCs without any sign of invasion [9,23,24,25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposals of TIGC management also include programs with different treatments according to TIGC number and size, performing surgery in cases of large polyps or frequently recurring multiple lesions, thus limiting a conservative approach to non-recurring cases of few small TIGCs [20,39]. On the other hand, promising results have been reported by SAs in selected patients having small multiple TIGCs without any sign of invasion [9,23,24,25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…Gastric surgery has been proposed for multiple or large lesions, or for patients with recurrence after endoscopic resection, in order to definitively stop hypergastrinemia by antrectomy, or radically remove TIGC by total gastrectomy [9,20,21,22]. Somatostatin analogs (SAs) have also been proposed as they decrease tumor growth both in vitro and in vivo [9,23,24,25,26,27]. A further alternative evaluated is the conservative management by serial endoscopic controls and lesion removal; however, among the few studies evaluating this option, most of them are based on small sample sizes, include patients managed by different strategies and in addition to this, recurrence data are scanty [9,11,12,13,17,22,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Somatostatin analogues reduce hypergastrinemia and have a direct antiproliferative effect on ECL cells. Although SSA are not yet recommended for types 1 and 2 GNETs, several case reports or cohort studies have reported reduction or disappearance of tumours treated with SSA (25,26,29,30). Even if SSA are considered as an over-treatment for types 1 and 2 GNETs, it is admitted that for selected cases SSA can be used, especially when endoscopic management is not feasible or not accepted by patients (31).…”
Section: Resultsmentioning
confidence: 99%
“…28,29 Limited studies, including a few small prospective studies, have demonstrated regression or complete disappearance of tumors and marked decrease in serum gastrin, lasting up to several years. [30][31][32][33][34][35][36][37][38][39] SSAs (e.g. octreotide and lanreotide) can be considered in cases in which endoscopic resection is not feasible due to extensive multifocal disease, or submucosal/lymph node involvement, as well as recurrent disease after repeated endoscopic resection.…”
Section: Medical Managementmentioning
confidence: 99%